Estudo e desenvolvimento da estratégia de controle de um gerador elétrico acionado por motor a pistão livre - Melo, Gabriel Antônio Martins Pereira de (2020)
The use of alternative energy sources is a important aim of the society and its scientific community. In the national scenario, the growing studies on this subject have as objective not only increasing the availability of electricity in the country, but also increase of Brazilian energy security. In this context, the technology of linear generators driven by free piston engine emerges as a viable solution. Within the scope of a great research project on linear generators, it is necessary the design of the closed loop movement control system of the linor, which could be comprehended as the planification of the rotor speed on rotative engines. The developed control strategy aimed to maximize the efficiency of the assembly, making the operation of the machine more stable and tolerant to variations up to 12,5% in the combustion force imposed by the burning of the gases used as fuel. Techniques and control strategies based on linor position were designed, which defines its maximum displacement controlling the variation of the current induced in the generator coils. The semi-active control technique based on PID and its variations was studied, in which the force of control does not actuate directly over the disturbance and by which the effectiveness of the control was demonstrated via the changing of the electrical charge associated with the generator. Besides, the techniques based on the switching of power semiconductors were studied, which also acted changing the electrical charge perceived by the generator. The action of these semiconductors was explored in the DC-DC conversion topologies, buck and boost models. The control of the linor movement made from the changing of the electrical charge associated with the generator demonstrated greater reliability and stability when the DC-DC converter boost model was applied. All the studied control techniques were evaluated according to the accuracy in the control of the state variables, the control effort and the robustness face to the non-uniform characteristic of the excitation force. From the scientific point of view, as already mentioned, the use of linear generators still requiring studies, capable to overcome the technological challenges encountered.